Performance of Shariah vs Non-Shariah Firms: A Study of Manufacturing Sector in Malaysia - Kamal, Amjad Wajdi Noor Ahmad; Arshad, Ameer Irfhan; Che-Yahya, Norliza; Alyasa-Gan, Siti Sarah (Information Management and Business Review, 2023)
This research aims to examine the differences in the determinants of performance between Shariah-compliant and non-Shariah-compliant firms. The changes in the Shariah screening technique in Malaysia since 2013 have significantly affected how firms that comply with the Shariah principles, as opposed to non-compliant firms, leading to the motivation of this research being conducted. This research employs panel data regression analysis to test its hypotheses. Compiling data from 142 manufacturing firms (71 Shariah-compliant and 71 non-Shariah-compliant firms) from 2012 to 2021, this research found that Shariah-compliant firm performance is significantly influenced by firm size, leverage, tangibility and efficiency. In contrast, non-Shariah-compliant firm performance is significantly influenced by leverage, tangibility, working capital and efficiency. This research contributes to relevant parties, such as the manufacturing firms and policymakers, in providing insights on the most relevant indicators affecting firm performance, specifically those in the manufacturing sector.